Epidemiologic features of non-alcoholic fatty liver disease in Russia - O. M. Drapkina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate prevalence nonalcoholic fatty liver disease (NAFLD) with assessment of age dynamics of distribution, interrelation of stages and value of clinical cardio-vascular markers in patients addressing for medical aid to physicians of polyclinics of Russia.Material and methods. First Russian epidemiologic observational study DIREG L 01903 on prevalence of non-alcoholic fatty liver disease was carried out in the Russian Federation in 2007. Overall 30 754 patients (56% of women, 44% of men) in the age of 18 to 80 years who sought medical attention of municipal polyclinics irrespective of the reference reason (either with subjective symptoms of liver disease or in the absence of those) have been investigated in 208 large medical centers for 8 months. Investigation included general (anthopometrical), laboratory and instrumental investigations, such as assessment of hepatites B and C markers, liver transaminases, gamma-glutamyltranspeptidase, blood lipid spectrum, glucose level, and abdominal ultrasound investigation, if required — esophagogastroduodenoscopy. In 4–6 wks at the second visit of the patient biochemical tests were repeated or supplemented with tests for alkaline phosphatase, bilirubin, albumin, gammaglobulin, serum iron.Results. The prevalence of NAFLD among adult population of the Russian Federation was 27%, including 80,3% of hepatic steatosis cases, 16,8% — nonalcoholic steatohepatitis and 2,9% — liver cirrhosis. Frequency of NAFLD detection increase by the age of 50. In the age group of 50–59 years the prevalence of disease reached the highest values, making 31,1% among the whole screened population. The impact of all studied risk factors of cardio-vascular diseases (р<0,001) has been found. The major risk factors revealed in NAFLD patients population, were systemic hypertension (69,9%), abdominal obesity (56,2%), hypercholesterolemia (68,8%).Conclusions. Prevalence of NAFLD among adult population of Russia is very high: almost every third patient who was looking for medical attention in polyclinic, has one of NAFLD-related disease entities. Metabolic syndrome and its components have been determined as leading risk factors of this disease, that once again emphasizes significance of interrelation of cardio-vascular diseases and NAFLD. Therefore, development of management approach and search of effective treatment should be carried out in two directions — for liver and cardiac diseases.